Teacher Professionalism in the Midst of Curriculum Dynamics and Educational Technology - Feby Aulia; Sofie Raihana Tampubolon; Tri Putri Handayani (International Journal of Educational Practice and Policy, 2025)
Teachers have a strategic role in educating the nation's life and shaping the character of the nation's next generation. Technological developments, curriculum changes, and the diversity of students require teachers to continue to improve their professionalism. This study aims to examine the characteristics of professional teachers, professional duties, challenges faced, and strategies to improve the quality of the teaching profession in the modern era. The method used is a literature study of journals and scientific articles published between 2020 and 2025. The results show that professional teachers have pedagogical, personality, social, and professional competencies, as well as moral responsibility, commitment to the profession, and involvement in professional organizations. Teachers' duties cover professional, humanitarian and social domains. Key challenges include mastery of digital technologies, digital ethics and developing 21st century skills in students. Suggested strategies include continuous training, collaboration among teachers, administrative efficiency, and improved welfare. With a good understanding of professionalism and the code of ethics, teachers are expected to optimally carry out their role as agents of educational change.